The COMPASS subunit Spp1 protects nascent DNA at the Tus/Ter replication fork barrier by limiting DNA availability to nucleases - Nagham Ghaddar; Yves Corda; Pierre Luciano; Martina Galli; Ylli Doksani; Vincent Géli (Nature Communications, 2023)
Abstract Homologous recombination factors play a crucial role in protecting nascent DNA during DNA replication, but the role of chromatin in this process is largely unknown. Here, we used the bacterial Tus/Ter barrier known to induce a site-specific replication fork stalling in S. cerevisiae. We report that the Set1C subunit Spp1 is recruited behind the stalled replication fork independently of its interaction with Set1. Spp1 chromatin recruitment depends on the interaction of its PHD domain with H3K4me3 parental histones deposited behind the stalled fork. Its recruitment prevents the accumulation of ssDNA at the stalled fork by restricting the access of Exo1. We further show that deleting SPP1 increases the mutation rate upstream of the barrier favoring the accumulation of microdeletions. Finally, we report that Spp1 protects nascent DNA at the Tus/Ter stalled replication fork. We propose that Spp1 limits the remodeling of the fork, which ultimately limits nascent DNA availability to nucleases.